(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Behavioral Science can use lay terms to understand and intervene in the world as long as these terms are operationalized in a behavioral conceptualization. The concept of “values” has been adressed by authors of the area, both by theoretical researchers and clinical practitioners. And as an element that underlies the practice of the behavior analyst, the concept’s comprehension in a behavior-analytic framework becomes relevant. Thus, based on the literature of Behavior Analysis, more specifically verbal behavior, contingencies of social reinforcement and symbolic behavior, the purpose of this article is to investigate the conceptual development of the term “values” and some of its implications for the practice of the behavior-analytic therapist